Fraxinol attenuates LPS-induced acute lung injury by equilibrating ACE-Ang II-AT1R and ACE2-Ang (1-7)-Mas and inhibiting NLRP3 - Yan Wu; Xin Yang; Yuanyuan Ju; Fei Zhao (Taylor & Francis Group, 2022)
Context Acute lung injury (ALI) is a serious heterogenous pulmonary disorder. Fraxinol was selected for this study since it is a simple coumarin compound, not previously investigated in ALI.Objectives This study investigates the ALI therapeutic effect and mechanisms of fraxinol.Materials and methods Male BALB/c mice were treated with fraxinol (20, 40, and 80 mg/kg) following intranasal injection of lipopolysaccharide (LPS; 10 μg in 50 μL). The mice in control group were intratracheally injected with 50 μL phosphate buffered saline (PBS). Raw264.7 cells were treated with fraxinol by 100 ng/mL LPS for 6 h, then treated by different concentrations of fraxinol (5, 10, and 25 μM) for 48 h. Cells in control group were treated with PBS.Results Fraxinol with doses of 20, 40, and 80 mg/kg significantly attenuated LPS-induced lung injury in mice (lung injury score, 10.4, 31.2, 50.3%). Fraxinol attenuated the apoptosis and nucleotide-binding oligomerization domain-like receptor family pyrin domain-containing-3 (NLRP3) activation induced by LPS (apoptosis, 18.3, 30.2, 55.6%; NLRP3, 30.0, 47.7, 63.6%). The anti-apoptosis and anti-inflammation effects of fraxinol were also confirmed in Raw264.7 cells (apoptosis, 38.8, 55.3, 68.9%; NLRP3, 20.6, 55.7, 73.9%).Discussion and conclusion The anti-ALI effects of fraxinol maybe by equilibrating ACE-Ang II-AT1R and ACE2-Ang (1-7)-Mas axis and inhibiting NLRP3 inflammasome. Our research provides a candidate drug in the treatment of ALI.